2020
DOI: 10.1021/acs.jmedchem.0c00812
|View full text |Cite
|
Sign up to set email alerts
|

Dienone Compounds: Targets and Pharmacological Responses

Abstract: The biological responses to dienone compounds with a 1,5-diaryl-3-oxo-1,4-pentadienyl pharmacophore have been studied extensively. Despite their expected general thiol reactivity, these compounds display considerable degrees of tumor cell selectivity. Here we review in vitro and preclinical studies of dienone compounds including b-AP15, VLX1570, RA-9, RA-190, EF24, HO-3867, and MCB-613. A common property of these compounds is their targeting of the ubiquitin–proteasome system (UPS), know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 156 publications
(560 reference statements)
1
32
0
Order By: Relevance
“…Previous reports described a similar sensitivity of TP53 ‐wild type and TP53‐ mutant cell lines to b‐AP15. Bazzaro et al indicated that IC 50 of TP53 ‐wild type cell lines in the NCI 60 panel to b‐AP15 is 0.18 μmol/L, and IC 50 of TP53‐ mutant cell lines is 0.15 μmol/L ( P = .70) 49 . Didier et al reported that b‐AP15 has an antitumor effect irrespective of mutation status on BRAF , NRAS , and TP53 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports described a similar sensitivity of TP53 ‐wild type and TP53‐ mutant cell lines to b‐AP15. Bazzaro et al indicated that IC 50 of TP53 ‐wild type cell lines in the NCI 60 panel to b‐AP15 is 0.18 μmol/L, and IC 50 of TP53‐ mutant cell lines is 0.15 μmol/L ( P = .70) 49 . Didier et al reported that b‐AP15 has an antitumor effect irrespective of mutation status on BRAF , NRAS , and TP53 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Bazzaro et al indicated that IC 50 of TP53 ‐wild type cell lines in the NCI 60 panel to b‐AP15 is 0.18 μmol/L, and IC 50 of TP53‐ mutant cell lines is 0.15 μmol/L ( P = .70). 49 Didier et al reported that b‐AP15 has an antitumor effect irrespective of mutation status on BRAF , NRAS , and TP53 . 9 D'Arcy et al reported using isogenic clones of HCT‐116 that b‐AP15 induced apoptosis that was insensitive to overexpression of Bcl‐2 and disruption of TP53.…”
Section: Discussionmentioning
confidence: 99%
“…RA413S and RA414 also both show stronger binding to their 42kDa protein target, previously identified as RPN13, in ovarian cancer cell lysates than RA183. Although these reactive compounds have potential for off-target effects [50], RA190 and related inhibitors bind to cysteine 88 within a groove of RPN13 that mediates binding to the proteasome via RPN2 [16,17]. This suggests that drug blockade of RPN13 association to the 19S RP inhibits both proteasomal degradation and deubiquitinase activity of its binding partner UCH37.…”
Section: Discussionmentioning
confidence: 99%
“…So manual test is feasible, but for a limited number of samples. We took ten articles [28][29][30][31][32][33][34][35][36][37] to test our method on the real data. Structures that represent reaction mechanisms were excluded, so we regarded only molecules and Markush templates.…”
Section: Validation On Real Datamentioning
confidence: 99%